PENGARUH KECERDASAN EMOSIONAL, STATUS SOSIAL EKONOMI ORANG TUA, DAN DUKUNGAN SOSIAL TEMAN SEKOLAH PADA TINGKAT PEMAHAMAN PELAJARAN AKUNTANSI DI SMK NEGERI 2 TUBAN - Kusnita, Eny (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2017)
The purpose of the research was to analyze the effect of emotional intelligence, socio-economic status of parents, and schoolmate social support in the understanding grade of accounting subject at SMK Negeri 2 Tuban. The population of this research XI class students accounting competence 2013/2014 consist of 86 students who were using proportional random sampling technique. This study used a quantitative approach to data analysis techniques through multiple linear regressions. The results of this study show simultaneously emotional intelligence, parents socio-economic status, and schoolmates social support influence to the the level of understanding of accounting subjects. But partially insignificant is the socio-economic parents status to the understanding level of accounting subject